Unsaturated polyester-kenaf composites: The effects of a modified montmorillonite filler on the tensile properties - R. H., Din; Luqman, Musa; A. A., Musa; Tay, G. -S. (Taylor & Francis Group, LLC., 2010)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/